2021
DOI: 10.1111/aor.13930
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold‐free tissue‐engineered arterial grafts derived from human skeletal myoblasts

Abstract: Tissue-engineered vascular grafts (TEVGs) are in urgent demand for both adult and pediatric patients. Although several approaches have utilized vascular smooth muscle cells (SMCs) and endothelial cells as cell sources for TEVGs, these cell sources have a limited proliferative capacity that results in an inability to reconstitute neotissues.How to cite this article: Saito J, Yokoyama U, Nakamura T, et al. Scaffold-free tissue-engineered arterial grafts derived from human skeletal myoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Therefore, in this study, the hardness increase of cell sheets seems to be due to the increase of F-actin expression. On the other hand, collagen secretion is an effective method used to engineer texture which can be achieved with cytokine 34 or mechanical stimulation 35 . In addition, it is possible to further improve texture via long-term culture, manipulation of myoblast orientation, myotube formation 36 , and electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, the hardness increase of cell sheets seems to be due to the increase of F-actin expression. On the other hand, collagen secretion is an effective method used to engineer texture which can be achieved with cytokine 34 or mechanical stimulation 35 . In addition, it is possible to further improve texture via long-term culture, manipulation of myoblast orientation, myotube formation 36 , and electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, using autologous cells, such as, endothelial and smooth muscle cells, still present several hurdles like limited harvesting potential and the inability to reconstitute neo-tissues due to poor ex vivo differentiation and expansion rates. To overcome these limitations, the use of human skeletal myoblasts has been proposed as an alternative cell source, taking advantage of their high in vitro proliferative capacity ( Saito et al, 2021 ). Another approach could rely on the generation of autologous induced pluripotent stem cells from peripheral blood-derived mononuclear cells and inducing their differentiation towards endothelial and smooth muscle cells to develop TEVGs.…”
Section: Tissue-engineered Vascular Graftsmentioning
confidence: 99%
“…On the downside, these grafts are expensive and have a long production time ranging from six to nine months [51]. However, recent studies by Jung et al [50] and Saito et al [53] have shown the feasibility of reducing production time to as low as 35 to 48 days using stem cells or progenitor cells [50,53].…”
Section: Scaffold-free Techniquesmentioning
confidence: 99%